2022
DOI: 10.1002/ar.25135
|View full text |Cite
|
Sign up to set email alerts
|

Moxibustion improved the effect of fecal microbiota transplantation donor to dextran sulfate sodium‐induced colitis in mice

Abstract: Fecal microbiota transplantation (FMT) is beneficial for several gastrointestinal diseases because it alters the intestinal microbiota of recipients. The efficacy of FMT is related to the microbial structure and composition of the donor. Mild moxibustion is a non‐invasive and safe traditional Chinese therapy that can regulate the gut microbiota. In this study, we investigated whether moxibustion improved the efficacy of FMT in donors using a dextran sulfate sodium (DSS)‐induced colitis mouse model. Normal mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…A previous study found that moxibustion has a certain ability to regulate the gut microbiota (Wei et al, 2019). In this issue, the authors led by Wang (Wang, Wu, et al, 2023), found that the application of moxibustion on Tianshu (ST25) and Zusanli (ST36) acupoints significantly improved weight loss, inflammation, abnormal microbial community composition, and the relative abundance of certain bacteria in a mouse model of ulcerative colitis induced by dextran sulfate sodium (DSS). Their findings might provide new strategies for selectively targeting fecal microbiota transplantation donors.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study found that moxibustion has a certain ability to regulate the gut microbiota (Wei et al, 2019). In this issue, the authors led by Wang (Wang, Wu, et al, 2023), found that the application of moxibustion on Tianshu (ST25) and Zusanli (ST36) acupoints significantly improved weight loss, inflammation, abnormal microbial community composition, and the relative abundance of certain bacteria in a mouse model of ulcerative colitis induced by dextran sulfate sodium (DSS). Their findings might provide new strategies for selectively targeting fecal microbiota transplantation donors.…”
Section: Introductionmentioning
confidence: 99%